Resistance-Nodulation-Division Efflux Pump, LexABC, Contributes to Self-Resistance of the Phenazine Di-N-Oxide Natural Product Myxin in Lysobacter antibioticus - Zhao, Yangyang; Liu, Jiayu; Jiang, Tianping; Hou, Rongxian; Xu, Gaoge; Xu, Huiyong; Liu, Fengquan (Frontiers in Microbiology, 2021)
Antibiotic-producing microorganisms have developed several self-resistance mechanisms to protect them from autotoxicity. Transporters belonging to the resistance- nodulation-division (RND) superfamily commonly confer multidrug resistance in Gram-negative bacteria. Phenazines are heterocyclic, nitrogen-containing and redox-active compounds that exhibit diverse activities. We previously identified six phenazines from Lysobacter antibioticus OH13, a soil bacterium emerging as a potential biocontrol agent. Among these phenazines, myxin, a di-N-oxide phenazine, exhibited potent activity against a variety of microorganisms. In this study, we identified a novel RND efflux pump gene cluster, designated lexABC, which is located far away in the genome from the myxin biosynthesis gene cluster. We found a putative LysR-type transcriptional regulator encoding gene lexR, which was adjacent to lexABC. Deletion of lexABC or lexR gene resulted in significant increasing susceptibility of strains to myxin and loss of myxin production. The results demonstrated that LexABC pump conferred resistance against myxin. The myxin produced at lower concentrations in these mutants was derivatized by deoxidation and O-methylation. Furthermore, we found that the abolishment of myxin with deletion of LaPhzB, which is an essential gene in myxin biosynthesis, resulted in significant downregulation of the lexABC. However, exogenous supplementation with myxin to LaPhzB mutant could efficiently induce the expression of lexABC genes. Moreover, lexR mutation also led to decreased expression of lexABC, which indicates that LexR potentially positively modulated the expression of lexABC. Our findings reveal a resistance mechanism against myxin of L. antibioticus, which coordinates regulatory pathways to protect itself from autotoxicity.